(untitled) (LEARNing Landscapes, 2014)
All children, regardless of ability, should feel valued and respected in their classroom. At times, the children who struggle miss out on purpose-driven, meaningful learning because they are classified by what they cannot do instead of honoured for what they can do. Through my narrative of Henry, I explore the importance of truly coming to know each student as a learner in the classroom. I begin by reflecting on my own experiences in school as a student and then as a beginning teacher. I then explore the use of the reader’s workshop model and discuss how I have used it as an approach to differentiated teaching and learning in a way that creates space for relationships to grow and students to be supported. Finally, I conclude by revisiting my story of Henry and reflect on how his story, and implementing the reader’s workshop model, will continue to affect my teaching as I grow both as a teacher and learner.